Higher adenoma detection, sessile serrated lesion detection and proximal sessile serrated lesion detection are associated with physician specialty and performance on Direct Observation of Procedural Skills - Lovedeep Gondara; Robert Enns; Jennifer Telford; Steven Pi; Laura Gentile (BMJ Open Gastroenterology)
Objective Adenoma detection rate (ADR) and sessile serrated lesion detection rate (SSLDR) vary among physicians. We sought to determine physician characteristics associated with ADR and SSLDR in a population-based colon screening programme.Design Retrospective study of 50–74 year olds with positive faecal immunochemical test and colonoscopy from 15/11/2013 to 31/12/2018. Physician characteristics included: gender, specialty, year and country of medical school graduation, colonoscopy volume and Direct Observation of Procedural Skills (DOPS) performance. Multivariable regression was performed on the following dependent variables: ADR, advanced ADR, proximal and distal ADR, SSLDR, proximal and distal SSLDR.Results 104 326 colonoscopies were performed by 261 physicians. A higher ADR was associated with gastroenterology (OR for general surgery 0.87, 95% CI 0.80 to 0.95; OR for general/family/internal medicine 0.70, 95% CI 0.55 to 0.88), fewer years since graduation (OR for graduation >2000 10.48, 95% CI 1.30 to 1.69 compared with <1980) and DOPS performance (OR for lowest DOPS performance 0.64, 95% CI 0.50 to 0.82 compared with highest DOPS performance). SSLDR was associated with gastroenterology (OR for general surgery 0.89, 95%, CI 0.81 to 0.97; OR for general/family/internal medicine 0.67, 95% CI 0.49 to 0.92) and DOPS performance (OR for lowest DOPS performance 0.71, 95% CI 0.51 to 0.99 compared with highest DOPS performance). Proximal SSLDR was associated with gastroenterology (OR for general surgery 0.90, 95% CI 0.82 to 0.99; OR for general/family/internal medicine 0.69, 95% CI 0.50 to 0.97) and DOPS performance (OR for lowest DOPS performance 0.68, 95% CI 0.47 to 0.99).Conclusion Higher ADR, SSLDR and proximal SSLDR was associated with gastroenterology specialty and improved performance on DOPS.